2018
DOI: 10.1021/jacs.8b12335
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Electronic Perturbations of CuA Centers via Subtle Geometric Changes

Abstract: CuA is a binuclear copper site acting as electron entry port in terminal heme-copper oxidases. In the oxidized form, CuA is a mixed valence pair whose electronic structure can be described using a potential energy surface with two minima: σu* and πu, that are variably populated at room temperature. We report that mutations in the first and second coordination spheres of the binuclear metallocofactor can be combined in an additive manner to tune the energy gap and, thus, the relative populations of the two lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 39 publications
5
22
0
Order By: Relevance
“…Overall, these results show that the mechanism of substrate–O 2 coupling can be effected through rearrangement of the copper coordination geometry and subsequent changes in the d-orbital electronics, with minimal change in the rest of the protein backbone structure. These results underline recent observations in other copper proteins ( 60 ) that minimal structural changes can be coupled to large electronic changes at the copper active site.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, these results show that the mechanism of substrate–O 2 coupling can be effected through rearrangement of the copper coordination geometry and subsequent changes in the d-orbital electronics, with minimal change in the rest of the protein backbone structure. These results underline recent observations in other copper proteins ( 60 ) that minimal structural changes can be coupled to large electronic changes at the copper active site.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the introduction of the Met160His mutation into the Tt-3L-Hs chimera to produce the Tt-3L-M160H variant results in a downshift of E 0 with respect to WT Tt-Cu A , which approximately corresponds to the sum of the downshifts induced by the individual first and second sphere modifications. 53 As discussed in the preceding section, inner and outer sphere mutations of the Tt-Cu A site result in modulation of , which is expected to have an impact on E 0 other than just coulombic stabilization/destabilization. Indeed, it was found that the reduction entropies of the different Tt-Cu A variants, including first and second sphere modifications, increase with .…”
Section: Redox Thermodynamics Of Cu Amentioning
confidence: 93%
“…50,54 Moreover, combined first and second coordination sphere modification was achieved by introducing the Met160His point mutation in the so-called Tt-3L-Hs chimera. 53 In all cases, the generated proteins were characterized by a variety of spectroscopic methods such as UV-vis, EPR, NMR, RR and EXAFS, which demonstrate that the structure and the mixed valence character of the Cu A site are preserved in all these variants. Interestingly, a comparison of the UV-vis spectra obtained experimentally and calculated by TD-DFT indicate that the different modifications alter the relative populations of the alternative σ u * and π u ground states, i.e.…”
Section: Table 1 Cu a Chimeras Constructed By Either Single Or Multiple Mutations Of Tt-cumentioning
confidence: 94%
See 1 more Smart Citation
“…17 Although in proteins the extensive network of residue contacts in active sites may compensate for improper modelling of metal-protein interactions, in small scaffolds the chemical environment around the metal ions needs to be properly defined. 18 On this regard, CED approaches are well-suited to address these issues since interactions of the metal ion with both the protein and substrates can be modelled explicitly.…”
Section: Introductionmentioning
confidence: 99%